Educational Innovation For The Future Through Fun Tutors Tutoring Program - Sholiyah, Sholiyah; Susanti, Novi; Nur Rochmah, Alyssa; Amalia Navi’ah, Risyda (LPPM Universitas Duta Bangsa Surakarta, 2023)
Fun Tutors is a tutoring business specialised for elementary school students and kindergarten children. This journal describes the Fun Tutors business concept as an innovative approach to future education. Fun Tutors is a type of tutoring that brings together education and entrepreneurship to create an innovative learning environment with engaging and fun learning. This journal examines the challenges and opportunities for the implementation of Fun Tutors Business in education, using a qualitative approach and direct observation. The findings observed problems with learning in education and problems with existing tutoring centres so as to change to more innovative teaching methods to prepare students for the demands of the future, and create tutoring centres that have effective and innovative methods. The feasibility analysis of the market and marketing aspects of Fun Tutors tutoring shows a very good prospect for the development of the tutoring business. Bimbel Fun Tutors has experienced teachers and experts in their fields. And the result of financial analysis using payback period shows that Fun Tutors tutoring takes 2 months and 8 days to return its capital.